JAK2-positive Philadelphia-negative myeloproliferative neoplasms - Anjali Sharma; Gurdeep Buxi; Sadhna Marwah; Rajbala Yadav (Wolters Kluwer Medknow Publications, 2011)
The recent discovery of the JAK2 mutations has rekindled interest in the approach to classic BCR/ABL-negative myeloproliferative neoplasms (MPNs) in terms of both diagnostic evaluation and treatment. However, additional clinical, laboratory and histological parameters play a key role to allow diagnosis and subclassification, regardless of whether JAK2 V617F mutation is present or not. Here are two cases which incidentally presented with splenomegaly and moderate leukocytosis, and were diagnosed as MPN-primary myelofibrosis (PMF) in prefibrotic phase and polycythemia vera (PV), respectively, using revised World Health Organization (WHO) 2008 criteria.